Penerapan Human-Centered Design Optimalisasi Desain Interior Puskesmas Baturiti 1 - Evangelina Maria De Fatima Brites Dos Santos; I Gusti Ayu Canny Utami; Ni Nyoman Sri Rahayu (Universitas Medan Area, 2026)
Community health centres play a strategic role in Indonesia’s primary healthcare system by providing various prevention programs, health promotion, and basic medical treatment. However, many Puskesmas facilities still face challenges in interior design, which affect patients comfort and the effectiveness of medical staff operations. These conditions lead to suboptimal healthcare services and user experience. Therefore, a design approach that prioritizes the users needs is essential to create a more functional and comfortable environment. One of the methods that can be applied is Human-Centered Design (HCD), which focuses on ergonomic, psychological and functional aspects to develop an interior design that better adapts to the needs of patients and healthcare workers. This approach not only enhances the aesthetic quality of the space but also improves operational efficiency and user comfort. This study explores the application of the HCD concept in optimizing the interior design of Puskesmas Baturiti 1. The methods used include direct observation, interviews, surveys, and literature analysis on healthcare facility design. The expected outcome of this research is to develop a interior design that enhances efficiency, improves lighting quality, and fosters an atmosphere that supports the comfort and productivity of both patients and medical personnel.